How Staying Negative Is Good for the (Adult) Brain: Maintaining Chloride Homeostasis and the GABA-Shift in Neurological Disorders - Hui, Kelvin K.; Chater, Thomas E.; Goda, Yukiko; Tanaka, Motomasa (Frontiers in Molecular Neuroscience, 2022)
Excitatory-inhibitory (E-I) imbalance has been shown to contribute to the pathogenesis of a wide range of neurodevelopmental disorders including autism spectrum disorders, epilepsy, and schizophrenia. GABA neurotransmission, the principal inhibitory signal in the mature brain, is critically coupled to proper regulation of chloride homeostasis. During brain maturation, changes in intracellular chloride concentration act to flip GABA signalling from excitatory to inhibitory for neuronal activation, and dysregulation of this GABA-shift likely contributes to multiple neurodevelopmental abnormalities that are associated with circuit dysfunction. Whilst traditionally viewed as a phenomenon which occurs during brain development, recent evidence suggests that this GABA-shift may also be involved in neuropsychiatric disorders due to the “dematuration” of affected neurons. In this review, we will discuss the cell signalling and homeostatic regulatory mechanisms underlying the GABA-shift phenomenon in the context of the latest findings in the field, in particular the role of chloride cotransporters NKCC1 and KCC2, and furthermore how these regulatory processes are altered in neurodevelopmental and neuropsychiatric disorders. We will also explore the interactions between GABAergic interneurons and other cell types in the developing brain that may influence the GABA-shift. Finally, with a greater understanding of how the GABA-shift is altered in pathological conditions, we will briefly outline recent progress on targeting NKCC1 and KCC2 as a therapeutic strategy against neurodevelopmental and neuropsychiatric disorders associated with improper chloride homeostasis and GABA-shift abnormalities.